Sunni-Syiah Conflict in Sampang, Madura: The Politics of Identity - Novita Maulida Ikmal (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2021)
The dominance of religious groups that occurred in Sampang, Madura, has caused prolonged conflict in 2012. Differences in beliefs related to the conception of religious practices in Islam make each group believe in their respective sect. This conflict led to riots between relatives and the community and resulted in the displacement of the Shiite group from their homes in Sampang Madura. Efforts to resolve the government by mediation with the aim of seeking peace are also not over. Various studies have revealed that the Sunni-Syiah conflict that occurred in Sampang is not only limited to theological differences but many factors that influence and are interrelated. The problem is, how can a group's identity dominate in the area so that it can kill minority groups? Qualitative research through in-depth interviews, observation, and document search through literature studies with analysis of the inner and outer ring of the chronology of conflict, actors, victims, motives, and networks have at least found a dominant group that shapes identity politics. Identity politics that emerged in Sampang, refers to the political mechanism of organizing identity, where political identity and social identity are sources and political means for a group. The Syiah conflict also leads to negative identity politics, it is seen that there is resistance to a new identity that appears in the community.